Real-world characterization of vestibular contributions during locomotion - Foulger, Liam H.; Charlton, Jesse M.; Blouin, Jean-Sébastien (Frontiers in Human Neuroscience, 2024)
The vestibular system, which encodes our head movement in space, plays an important role in maintaining our balance as we navigate the environment. While in-laboratory research demonstrates that the vestibular system exerts a context-dependent influence on the control of balance during locomotion, differences in whole-body and head kinematics between indoor treadmill and real-world locomotion challenge the generalizability of these findings. Thus, the goal of this study was to characterize vestibular-evoked balance responses in the real world using a fully portable system. While experiencing stochastic electrical vestibular stimulation (0-20 Hz, amplitude peak ± 4.5 mA, root mean square 1.25mA) and wearing inertial measurement units (IMUs) on the head, low back, and ankles, 10 participants walked outside at 52 steps/minute (~0.4 m/s) and 78 steps/minute (~0.8 m/s). We calculated time-dependent coherence (a measure of correlation in the frequency domain) between the applied stimulus and the mediolateral back, right ankle, and left ankle linear accelerations to infer the vestibular control of balance during locomotion. In all participants, we observed vestibular-evoked balance responses. These responses exhibited phasic modulation across the stride cycle, peaking during the middle of the single-leg stance in the back and during the stance phase for the ankles. Coherence decreased with increasing locomotor cadence and speed, as observed in both bootstrapped coherence differences (p < 0.01) and peak coherence (low back: 0.23 ± 0.07 vs 0.16 ± 0.14, p = 0.021; right ankle: 0.38 ± 0.12 vs 0.25 ± 0.10, p < 0.001; left ankle: 0.33 ± 0.09 vs 0.21 ± 0.09, p < 0.001). These results replicate previous in-laboratory studies, thus providing further insight into the vestibular control of balance during naturalistic movements and validating the use of this portable system as a method to characterize real-world vestibular responses. This study will help 2 This is a provisional file, not the final typeset article support future work that seeks to better understand how the vestibular system contributes to balance in variable real-world environments.